Risk of Zika microcephaly correlates with features of maternal antibodies - Robbiani, Davide F. (J Exp Med, 2019)
Zika virus (ZIKV) infection during pregnancy causes congenital abnormalities, including microcephaly. However, rates vary widely, and the contributing risk factors remain unclear. We examined the serum antibody response to ZIKV and other flaviviruses in Brazilian women giving birth during the 2015–2016 outbreak. Infected pregnancies with intermediate or higher ZIKV antibody enhancement titers were at increased risk to give birth to microcephalic infants compared with those with lower titers (P < 0.0001). Similarly, analysis of ZIKV-infected pregnant macaques revealed that fetal brain damage was more frequent in mothers with higher enhancement titers. Thus, features of the maternal antibodies are associated with and may contribute to the genesis of ZIKV-associated microcephaly.